2012
DOI: 10.1098/rspb.2012.1158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic change for earlier migration timing in a pink salmon population

Abstract: To predict how climate change will influence populations, it is necessary to understand the mechanisms, particularly microevolution and phenotypic plasticity, that allow populations to persist in novel environmental conditions. Although evidence for climate-induced phenotypic change in populations is widespread, evidence documenting that these phenotypic changes are due to microevolution is exceedingly rare. In this study, we use 32 years of genetic data (17 complete generations) to determine whether there has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(147 citation statements)
references
References 53 publications
2
143
2
Order By: Relevance
“…Genetic monitoring of this late-migrating marker locus (LMML) demonstrated that a selective event, first evident in brood year 1989, had reduced the abundance of the latemigrating subpopulation and that these demographic changes have persisted over the subsequent 13 generations. These results provided compelling evidence that the shifting phenology of Auke Creek pink salmon has a genetic basis (Kovach et al 2012). …”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Genetic monitoring of this late-migrating marker locus (LMML) demonstrated that a selective event, first evident in brood year 1989, had reduced the abundance of the latemigrating subpopulation and that these demographic changes have persisted over the subsequent 13 generations. These results provided compelling evidence that the shifting phenology of Auke Creek pink salmon has a genetic basis (Kovach et al 2012). …”
Section: Introductionmentioning
confidence: 70%
“…The temporal characteristics of the LMMA in adults were described previously (Kovach et al 2012), and we briefly present those results here so that comparisons can be made between adults and fry. In each generation from 1985 to 1989, the LMMA frequency increased substantially after the midpoint of the migration (Fig.…”
Section: Monitoring Of the Lmmamentioning
confidence: 99%
See 1 more Smart Citation
“…Currently it remains unclear whether the few examples that demonstrate observable adaptive evolution of traits in response to climate change (e.g., body size [43], migration timing [44], thermal responses [45]) are dictated by various independent genes (within their respective genetic networks), or by fewer key regulatory genes within their genetic or metabolic networks. This is important to consider since any changes in the 'upstream' network genes could have extensive and numerous effects on traits [37], and yet the network itself may also provide some redundancy and buffering against perturbations, whereby changes to regulatory genes do not influence the genes they regulate [46].…”
Section: Biochemical Reactions and Gene Expressionmentioning
confidence: 99%
“…For example, increases in sea surface temperatures due to greenhouse gas emissions are predicted to shrink the thermal habitats of salmon over vast regions of the North Pacifi c Ocean and adjacent seas (Welch et al 1998a, b;Azumaya et al 2007;Abdul-Aziz et al 2011;Kaeriyama et al 2012Kaeriyama et al , 2014. Nevertheless, salmon are capable of rapid microevolution that may allow them to adapt quickly (within one or two generations) to climate change (Kovach et al 2012). At present, total commercial catches of Pacifi c salmon around the Pacifi c Rim, dominated by pink salmon O. gorbuscha and chum salmon O. keta, are near the all-time high levels since record keeping began (NPAFC 2014).…”
Section: Introductionmentioning
confidence: 99%